Obtaining of Ni–Al layered double hydroxide by slit diaphragm electrolyzer - Kovalenko, Vadym; Kotok, Valerii (Eastern-European Journal of Enterprise Technologies, 2017)
Ni–Al layered double hydroxides are promising cathode materials for Ni–Cd, Ni–Fe and Ni–MeH accumulators with improved characteristics. However, they are prepared using batch methods which cannot guarantee the stability of their characteristics. The main aim of the present work was the development of a continuous method of electrochemical synthesis of highly active Ni–Al layered double hydroxide in a slit diaphragm electrolyzer (SDE). A study on the influence of current density and anolyte composition (NaOH or NaOH+Na2CO3 at different ratios) on the electrochemical properties of NI-Al hydroxide has been conducted. The LDH structure has been proven by means of X-ray diffraction analysis. It has been demonstrated that synthesis of Ni-Al LDH in SDE must be conducted at high current densities at which formation rate of hydroxyl anions would exceed the supply rate of cations. This would prevent the presence of aluminum cations in the solution that causes poisoning upon adsorption on the hydroxide surface. It has been demonstrated that introduction of sodium carbonate into the anolyte is not feasible, because of the possibility of complete hydrolysis of Al3+ in the presence of СО32– with the formation of the Al(OH)3 phase. This phase is capable of dissolving in alkaline electrolyte and poisoning the nickel hydroxide electrode. Optimal parameters for the synthesis of Ni–Al LDH in SDE have been established: current density – 18 A/dm2, anolyte – NaOH solution. Ni–Al LDH, synthesized in SDE at these conditions, demonstrated the specific capacity of 237 mA·h/g. This exceeds capacities of chemically synthesized Ni-Al LDH (211 mA·h/g) and industrial sample (185 mA·h/g).